Natural Extracellular Electron Transfer Between Semiconducting Minerals and Electroactive Bacterial Communities Occurred on the Rock Varnish - Ren, Guiping; Yan, Yingchun; Nie, Yong; Lu, Anhuai; Wu, Xiaolei; Li, Yan; Wang, Changqiu; Ding, Hongrui (Frontiers in Microbiology, 2019)
Rock varnish is a thin coating enriched with manganese (Mn) and iron (Fe) oxides. The mineral composition and formation of rock varnish elicit considerable attention from geologists and microbiologists. However, limited research has been devoted to the semiconducting properties of these Fe/Mn oxides in varnish and relatively little attention is paid to the mineral–microbe interaction under sunlight. In this study, the mineral composition and bacterial communities on varnish from the Gobi Desert in Xinjiang, China were analyzed. Results of principal components analysis and t–test indicated that more electroactive genera such as Acinetobacter, Staphylococcus, Dietzia and Pseudomonas gathered on varnish bacterial communities than on substrate rock and surrounding soils. We then explored the culture of varnish, substrate and soil samples in media and the extracellular electron transfer (EET) between bacterial communities and mineral electrodes under light/dark condition for the first time. Orthogonal electrochemical experiments demonstrated that the most remarkable photocurrent density of 6.1 ± 0.4 μA/cm2 was observed between varnish electrode and varnish microflora. Finally, based on Raman and 16S rRNA gene sequencing results, coculture system of birnessite and Pseudomonas (the major Mn oxide and one common electroactive bacterium in varnish) was established for mechanism study. A steadily growing photocurrent (205 μA at 100 h) under light was observed with a stable birnessite after 110 h. However, only 47 μA was generated in the dark control and birnessite was reduced to Mn2+ in 13 h, suggesting that birnessite helped deliver electrons instead of serving as an electron acceptor under light. Our study demonstrated that electroactive bacterial communities were positively correlated with Fe/Mn semiconducting minerals in varnish, and diversified EET process occurred on varnish under sunlight. These phenomena may influence bacterial community structure in natural environments over time.